Diseño y construcción de un controlador lógico programable PLC a base de un microcontrolador. - Abad Ayavaca, Walter Fernando (2009)
PLCs are electronic devices widely used in industrial automation. The history of PLCs dates back to the late 1960s, when the industry was looking for new electronic technologies to replace and make more efficient control systems based on electrical circuits with relays, switches and other components commonly used for the Control of combinational logic systems. The purpose of this project is to design and implement a programmable logic controller (PLC) based on a PIC microcontroller which will provide a power control system in its outputs and inputs can be census or perform some specific function, this device can be programmed Easily, it will have an LCD screen in order to visualize according to the program what in this one executes, will also have a system of communication towards a computer being able to be used to monitor the functions of the programmable logic controller (PLC). This design is a technological contribution for those people who make use of the present project, so it has been fulfilled with the investigative method that when starting to develop the thesis has been proposed, same that already is designed. The National University of Loja as an Education and Research organization through its Electronics Technology career, in its desire to improve teaching and learning processes, has allowed the design and implementation of a programmable logic controller (PLC) based on a PIC microcontroller , As a support tool to facilitate and assist both teachers and students who are educated in this Institution. GENERAL OBJECTIVE.                   Design and implement a programmable logic controller (PLC) based on a PIC microcontroller. SPECIFIC OBJECTIVES.  Provide experiences in the field of microprocessed systems, instrumentation and power electronics.  Develop the necessary software for the implementation of the automation process based on the proposed PLC.  Build with an option of low cost, the processes of automation and control that are generated in the Career, Area and the University as contribution to the society.  Contribute to the Area of ​​Energy, Industries and Non-Renewable Natural Resources with a viable technical solution in which to pre professional practices in the fields of power electronics, microcontrollers, programming and automation.